Features of Idebenone and Related Short-Chain Quinones that Rescue ATP Levels under Conditions of Impaired Mitochondrial Complex I - Erb, Michael; Hoffmann-Enger, Barbara; Deppe, Holger; Soeberdt, Michael; Haefeli, Roman H.; Rummey, Christian; Feurer, Achim; Gueven, Nuri (PLOS ONE, 2012)
Short-chain quinones have been investigated as therapeutic molecules due to their ability to modulate cellular redox reactions, mitochondrial electron transfer and oxidative stress, which are pathologically altered in many mitochondrial and neuromuscular disorders. Recently, we and others described that certain short-chain quinones are able to bypass a deficiency in complex I by shuttling electrons directly from the cytoplasm to complex III of the mitochondrial respiratory chain to produce ATP. Although this energy rescue activity is highly interesting for the therapy of disorders associated with complex I dysfunction, no structure-activity-relationship has been reported for short-chain quinones so far. Using a panel of 70 quinones, we observed that the capacity for this cellular energy rescue as well as their effect on lipid peroxidation was influenced more by the physicochemical properties (in particular logD) of the whole molecule than the quinone moiety itself. Thus, the observed correlations allow us to explain the differential biological activities and therapeutic potential of short-chain quinones for the therapy of disorders associated with mitochondrial complex I dysfunction and/or oxidative stress.